Development Search Engine Kernel to Prevent Indexing Hurtful Sites and Evaluation Performance - سرار حمود (Latakia University Journal -Engineering Sciences Series, 2022)
This research contains web search engine kernel to control hurtful sites and prevent indexing it. This research contain information about search in web , retrieval system , types of search engines and basic architectures of building search engines . It suggests architecture of search engine kernel to do final planner of search engine architecture ,It build parts of search engine and execute test to get results.